Empowerment Educational Program: Is it Effective on Improving Patient Safety Culture among Nurses? - David Ezakaden, Elizabeth; Solomon, Smriti G. (International Journal of Nursing and Medical Investigation, 2024)
The patient safety culture (PSC) focuses on the aspects of organizational culture that pertain to patient safety. It is defined as a pattern of individual and organizational behavior based on shared beliefs and values that continuously seeks to minimize patient harm that may result from the deliverance of care. Patient safety means no preventable injury to patients during health care and a low risk of unwanted harm. An acceptable minimum balances current knowledge, resources, and care context against the danger of non-treatment or other therapy. The ability to successfully motivate and mobilize oneself and others to attain favorable results in nursing practice and the workplace is referred to as empowerment. Nurse-perceived patient safety and quality of care were poor, and patient and professional nurse adverse occurrences were underreported in a cross-sectional survey. Hospitals can improve patient safety and quality of care by fostering a culture of patient safety and communicating adverse events. As per the review which provides empirical evidence on current initiatives in patient safety education to establish a culture of safety among health-care professionals and patients, the patient safety education program has the potential to enhance the PSC of those working in the health-care industry.